The efficacy of azithromycin combined with seven types of Chinese medicine injections in the treatment of Mycoplasma pneumoniae pneumonia in children: a systematic review and Bayesian network meta-analysis - Huang, Xinggui; Tao, Sian; Liu, Chenhao; Sun, Xiaoluo; Hao, Yule; Ma, Yuqi; Liu, Yi; Liu, Jibin (Frontiers in Pharmacology, 2024)
Mycoplasma pneumoniae pneumonia (MPP) stands out as the predominant community-acquired pneumonia in children 5 years of age or older. In recent decades, the annual rise in drug resistance rates of macrolide antibiotics, particularly azithromycin, has led to complex clinical treatment strate-gies and substantial healthcare costs associated with MPP. Chinese medicine injections (CMIs), rec-ognized as an effective supplementary therapy, are acknowledged by clinicians in China. It is neces-sary to explore the efficacy of azithromycin in combination with CMIs. Methods: Randomized controlled trials (RCTs) evaluating azithromycin in combination with seven types of CMIs for MMP in children were identified based on inclusion criteria and assessed using the revised Cochrane Risk of Bias Tool (RoB 2.0). R 4.3.1 and STATA 15.0 were employed to generate ranking probabilities and perform network meta-analysis. Competing interventions were ranked using the surface under the cumulative ranking (SUCRA) probabilities. Results: A comprehensive analysis was performed on 155 RCTs involving 15,014 patients and eight therapeutic strategies within this Bayesian network meta-analysis (BNMA). The results indicated that azithromycin (AZ) combined with seven types of CMIs was more effective than azithromycin alone in overall outcomes. Notably, azithromycin combined with Chuanhuning injection (AZ + CHN) achieved the highest ranking in improving the clinical effective rate (SUCRA, 80.89%); regarding secondary outcome measures, the azithromycin combined with Yanhuning injection (AZ + YHN) had the highest probability of improving four different outcomes: disappearance time of cough (SU-CRA,80.01%), disappearance time of pulmonary rale (SUCRA, 87.77%), disappearance time of fever (SUCRA, 95.70%), and disappearance time of pulmonary shadows in X‐ray (SUCRA, 97.34%); fur-thermore, the azithromycin combined with Qingkailing injection (AZ + QKL) was more likely to re-duce average hospitalization time (SUCRA, 94.60%). Conclusion: This study highlights the potential benefits of seven types of Chinese medicine injec-tions as adjunctive therapy for Mycoplasma pneumoniae pneumonia in children. However, further support and validation of these findings are needed through high-quality randomized controlled trials with larger sample sizes and double-blind designs.